A Novel NDUFS3 mutation in a Chinese patient with severe Leigh syndrome. Issue 12 (December 2018) - Lou, Xiaoting; Shi, Hao; Wen, Shumeng; Li, Yuanyuan; Wei, Xiujuan; Xie, Jie; Ma, Lin; Yang, Yanling; Fang, Hezhi; Lyu, Jianxin
Abstract Leigh syndrome is one of the most common subtypes of mitochondrial disease. Mutations in encoding genes of oxidative phosphorylation complexes have been frequently reported, of which, MTATP6 was one of the most frequently reported genes for Leigh syndrome. In this study, by using next-generation sequencing targeted to MitoExome in a patient with clinical manifestations of Leigh syndrome, two missense mutations ofNDUFS3 (c.418 C > T/p.R140W and c.595 C > T/p.R199W) were identified, of which c.418 C > T was novel. Functionally, the patient derived lymphoblastoid cells showed decreased amount of NDUFS3 and complex I assembly when compared with two control cells. AlthoughNDUFS3 mutations have been related to late onset Leigh syndrome, we found that the patient carrying these two mutations developed an early onset Leigh syndrome. To our knowledge, this is the second study on patient carryingNDUFS3 mutations. In conclusion, we identified a novel Leigh syndrome causingNDUFS3 mutation and expanded the clinical spectrum caused byNDUFS3 mutations in this study.